Genomic surveillance uncovers a pandemic clonal lineage of the wheat blast fungus. - Sergio M Latorre; Vincent M Were; Andrew J Foster; Thorsten Langner; Angus Malmgren; Adeline Harant; Soichiro Asuke; Sarai Reyes-Avila; Dipali Rani Gupta; Cassandra Jensen; Weibin Ma; Nur Uddin Mahmud; et al. (PLoS Biology)
Wheat, one of the most important food crops, is threatened by a blast disease pandemic. Here, we show that a clonal lineage of the wheat blast fungus recently spread to Asia and Africa following two independent introductions from South America. Through a combination of genome analyses and laboratory experiments, we show that the decade-old blast pandemic lineage can be controlled by the Rmg8 disease resistance gene and is sensitive to strobilurin fungicides. However, we also highlight the potential of the pandemic clone to evolve fungicide-insensitive variants and sexually recombine with African lineages. This underscores the urgent need for genomic surveillance to track and mitigate the spread of wheat blast outside of South America and to guide preemptive wheat breeding for blast resistance.